2018
DOI: 10.1109/tnsre.2018.2864935
|View full text |Cite
|
Sign up to set email alerts
|

Wrist Robot-Assisted Rehabilitation Treatment in Subacute and Chronic Stroke Patients: From Distal-to-Proximal Motor Recovery

Abstract: In this study, the recovery of proximal and distal segments in stroke patients who received distal training alone was investigated. Forty (20 subacute and 20 chronic) stroke patients were recruited to perform wrist robot-assisted rehabilitation training. The upper extremity, shoulder-elbow and wrist subsections of the Fugl-Meyer Assessment Scale were used to assess the motor recovery of distal and proximal segments. In addition, the Modified Ashworth Scale, the Motricity Index and the Box & Block test were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…For the FMA-SE, the average scores increased by 42.4% (post-assessment) and 54% (3MFU) in the robotic hand group, with the ratio of 41.1% (post-assessment) and by 44.8% (3MFU) in the robotic sleeve group. The motor improvements in the FMA-SE subscale for the robotic hand group confirmed that robotic support at the distal fingers could also benefit the proximal joint recovery (i.e., shoulder/elbow), similar to the observations reported in the literature [31, 64]. The motor gain achieved in the robotic hand group was comparable to that for the sleeve group where direct robotic supports were provided to the proximal joints.…”
Section: Discussionsupporting
confidence: 85%
“…For the FMA-SE, the average scores increased by 42.4% (post-assessment) and 54% (3MFU) in the robotic hand group, with the ratio of 41.1% (post-assessment) and by 44.8% (3MFU) in the robotic sleeve group. The motor improvements in the FMA-SE subscale for the robotic hand group confirmed that robotic support at the distal fingers could also benefit the proximal joint recovery (i.e., shoulder/elbow), similar to the observations reported in the literature [31, 64]. The motor gain achieved in the robotic hand group was comparable to that for the sleeve group where direct robotic supports were provided to the proximal joints.…”
Section: Discussionsupporting
confidence: 85%
“…Robot-assisted rehabilitation has become increasingly popular in recent decades, and there are more and more therapy concepts that attributed to various novel rehabilitation robots (Shields et al, 1997; DiCicco et al, 2004; Wege and Hommel, 2005; Hasegawa et al, 2008; Chiri et al, 2009; Tadano et al, 2010; Brokaw et al, 2011; In et al, 2011; Kadowaki et al, 2011; Ueki et al, 2012; Villafañe et al, 2017; Cerasa et al, 2018; Jakob et al, 2018; Mazzoleni et al, 2018; Pila et al, 2018). In robot-assisted rehabilitation, patients can receive standardized and repetitive training controlled by robot actuators (Takahashi et al, 2005; Chang and Kim, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These results prove the motion function recovery effect of the stroke patient with the exoskeleton in ADLs. And, most of current devices are large in size and need to be fixed and trained in specific positions [45] . The proposed exoskeleton is portable and could be worn when the wearers move around.…”
Section: Daily Activity Experimentsmentioning
confidence: 99%
“…It's well known that rehabilitation is a long-term progress [45] . A lightweight and comfortable exoskeleton robot with high degree of human-robot fusion can be better accepted by patients.…”
Section: Daily Activity Experimentsmentioning
confidence: 99%